2022
DOI: 10.1055/s-0043-1761219
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship in Neuroanesthesia and Neurocritical Care

Abstract: In learning you will teach, and in teaching you will learn"-Phil Collins Challenges faced by healthcare professionals in their personal and professional life are aplenty. Facing them effectively requires following the footsteps of and learning from the experiences of role models, seniors, and colleagues, alike. A successful healthcare professional is one who is most likely mentored for such challenges through the various phases of his/her educational path and even further.Various definitions exist for the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The mentors may be a part of the teaching faculty to whom a student is assigned, and they must provide career advancement suggestions and psycho-social support. [ 9 ] Studies have concluded that mentorship programmes improve postgraduate students’ theoretical, clinical, and professional achievement. [ 10 ] Mentorship programmes in India are implemented in very few institutes.…”
Section: Mentorship Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mentors may be a part of the teaching faculty to whom a student is assigned, and they must provide career advancement suggestions and psycho-social support. [ 9 ] Studies have concluded that mentorship programmes improve postgraduate students’ theoretical, clinical, and professional achievement. [ 10 ] Mentorship programmes in India are implemented in very few institutes.…”
Section: Mentorship Programmesmentioning
confidence: 99%
“…Training Methods: Challenges remain in training teachers, adopting modern teaching methods, and maintaining the integration of e-learning platforms beyond exceptional circumstances. [ 13 ]…”
Section: Challengesmentioning
confidence: 99%